2021
DOI: 10.1186/s41476-021-00163-w
|View full text |Cite
|
Sign up to set email alerts
|

Graphene saturable absorbers applications in fiber lasers

Abstract: Two-dimensional materials are widely used in a variety of fields, such as medical treatment, industrial preparation, machining, etc. In this review, we have made a detailed description of the development of fiber lasers as well as the evolution of two-dimensional materials, especially graphene. In addition, we describe the optical properties of graphene and its preparations, for instance, chemical exfoliatio, liquid phase exfoliation, electrochemical technique, chemical vapor deposition, supercritical fluid ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 177 publications
0
13
0
Order By: Relevance
“…Light emitting applications (LED, laser) and other applications. So far, graphene-based ultrashort-pulse lasers have been exploited tremendously owing to their nonlinear absorption property by different types of lasers, including fiberbased, 35,193 solid-state, 194,195 and waveguide lasers. 196 B. Fu et al showed ultrafast broadband graphene fiber lasers covering 1, 1.5, and 2 mm wavelengths.…”
Section: Fabrication Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Light emitting applications (LED, laser) and other applications. So far, graphene-based ultrashort-pulse lasers have been exploited tremendously owing to their nonlinear absorption property by different types of lasers, including fiberbased, 35,193 solid-state, 194,195 and waveguide lasers. 196 B. Fu et al showed ultrafast broadband graphene fiber lasers covering 1, 1.5, and 2 mm wavelengths.…”
Section: Fabrication Processmentioning
confidence: 99%
“…Graphene, the firstly discovered 2D material, has been extensively studied and applied to versatile optical and electronic devices because of its exceptional thermal and electrical conductivity with flexibility. [34][35][36] Black phosphorous (BP) is an emerging 2D material that has distinctive material properties, which include not only high conductivity and carrier mobility but also tunable direct band-gap, unlike graphene. This tunable band-gap of BP enables a wide range of devices applications.…”
Section: Introductionmentioning
confidence: 99%
“…A. Absorptive nonlinear optics of graphene: Opportunities and challenges Graphene performs very well as a fast saturable absorber and has already been embedded in various fibe laser setups to obtain pulsed operation, either in the modelocked or Q-switched regime (Guo et al, 2019;Peng and Yan, 2021). As pointed out in Sec.…”
Section: Exploiting Graphene's Nonlinear Optics: Opportunities and Re...mentioning
confidence: 99%
“…[ 107 ] Both CNTs and graphene are equipped with outstanding properties including low cost, easy fabrication, and fast response time, making them ideal candidates to generate ultrafast pulses. [ 108 ]…”
Section: Applications Of Nanomaterials In Ultrafast Lasersmentioning
confidence: 99%